A SIAT3HE model of the COVID-19 pandemic in Bergamo, Italy. Issue 15 (2021) - Polver, Marco; Previdi, Fabio; Mazzoleni, Mirko; Zucchi, Alberto
Abstract: The aim of this article is to give a better understanding of the dynamics of the SARS-CoV-2 pandemic in the Bergamo province (Italy), one of the most hit areas of the world, between February and April 2020. A new compartmental model, called SIAT 3 HE, was designed and fitted on accurate data about the pandemic provided by ATS Bergamo, the health protection agency of the Bergamo province. Our results show that SARS-CoV-2 reached Bergamo in January and infected 318, 000 people, the 28.8% of the province population. The 43.1% of the infected individuals stayed asymptomatic. As 6, 028 people died due to COVID-19 till April 30th, the infection fatality ratio of SARS-CoV-2 in the Bergamo province was 1.9%. These results are in very good agreement with available information: the number of infections is consistent with the results of recent serological surveys and the number of deaths due to COVID-19 is close to the excess mortality of the considered period.